A strategy to improve resource utilization: Case study of generic drug distribution in Rajasthan. (2020) - Dixit, Anuj; Routroy, Srikanta; Kumar Dubey, Sunil
Abstract: The establishment of standard, universal and quality healthcare service is essential for developing countries such as India to enhance the quality of life. Various healthcare schemes such as Jan Aushadhi Scheme, Mukhyamantri Nishulk Dava Yojna etc are operating in India which provides free healthcare services including free distribution of medicines. The medicines provided in these schemes are mostly generic drugs and the supply chain has already been established for it. The variety of generic drugs varies in quantity across different storage points and consumption points, and also having different self-lives, costs and logistics requirements. It was observed that the performance of these supply chain needs to be improved in various dimensions. Therefore, generic drug distribution in Rajasthan is studied and analyzed in the current study. The different aspects of generic drug distribution considered in the study are process view of the existing supply chain, sourcing, ordering and procurement, logistics and warehousing, inventory management and information system. The use of various techniques such as value stream mapping, inbuilt analytical tool for ordering, 5S practice and performance measurement system is explored to develop a strategy for improved resource utilization.